Computational Mechanics of Polymeric Materials PEEK and PEKK Compared to Ti Implants for Marginal Bone Loss Around Oral Implants. - Afazal, Mohammad; Afreen, Saba; Anand, Vaibhav; Chanda, Arnab (Prosthesis (2673-1592), 2025)
Background/Objectives: Dental practitioners widely use dental implants to treat traumatic cases. Titanium implants are currently the most popular choice among dental practitioners and surgeons. The discovery of newer polymeric materials is also influencing the interest of dental professionals in alternative options. A comparative study between existing titanium implants and newer polymeric materials can enhance professionals' ability to select the most suitable implant for a patient's treatment. This study aimed to investigate material property advantages of high-performance thermoplastic biopolymers such as PEEK and PEKK, as compared to the time-tested titanium implants, and to find the most suitable and economically fit implant material. Methods: Three distinct implant material properties were assigned—PEEK, PEKK, and commercially pure titanium (CP Ti-55)—to dental implants measuring 5.5 mm by 9 mm, along with two distinct titanium (TI6AL4V) abutments. Twelve three-dimensional (3D) models of bone blocks, representing the mandibular right molar area with Osseo-integrated implants were created. The implant, abutment, and screw were assumed to be linear; elastic, isotropic, and orthotropic properties were attributed to the cancellous and cortical bone. Twelve model sets underwent a three-dimensional finite element analysis to evaluate von Mises stress and total deformation under 250 N vertical and oblique (30 degree) loads on the top surface of each abutment. Results: The study revealed that the time-tested titanium implant outperforms PEEK and PEKK in terms of marginal bone preservation, while PEEK outperforms PEKK. Conclusions: This study will assist dental practitioners in selecting implants from a variety of available materials and will aid researchers in their future research.